Determinasi Faktor-faktor Keputusan Hedging dengan Instrumen Derivatif pada Perusahaan Manufaktur - Anindya Anggun Larasati; Erric Wijaya (University of Merdeka Malang, 2022)
This study was conducted to determine the effect of independent variables used such as leverage, liquidity, growth opportunity, firm size, and financial distress on hedging decisions with derivative instruments in manufacturing companies on the IDX for the 2017-2021 period. The data used is secondary data downloaded from the Indonesia Stock Exchange website and the company's official website in the research sample. In selecting the sample, this study used a purposive sampling technique. The sample used was 47 manufacturing companies listed on the IDX for the 2017-2021 period. Logistic regression analysis was used in this study to test the hypothesis of each variable used. The test results show that the variables of leverage, growth opportunity, and firm size have a positive influence on hedging decisions with derivative instruments, and financial distress has a negative influence on hedging decisions with derivative instruments, while liquidity has no effect on hedging decisions with derivative instruments.